Possible mechanism of inhibition of virus infectivity with nanoparticles - Khylko, O.L.; Rusinchuk, N.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
The possible mechanism of inhibition of virus infectivity with nanoparticles has been considered both theoretically and experimentally. It has been supposed that inhibition is caused by action of the nanoparticles on specific molecules at the virus surface. A nanoparticle located close to the virus leads to the drastic increase in the local field intensity at this surface. It, in turn, leads to deformation (or destruction) of molecules that are responsible for virus absorption into the cell. When majority of these molecules are deformed, the virus loses its ability to penetrate into the cell and to cause a decease. This mechanism has been studied theoretically by applying the methods of nanophysics and experimental studying the absorption spectra of biological samples.